ダイ16ジ ナンキョク チイキ カンソクタイ エットウタイ ホウコク 1975-1976 - 星合, 孝男; ホシアイ, タカオ; HOSHIAI, Takao (国立極地研究所, 1978)
P(論文) 隊員30名からなる16次越冬隊は,1975年2月1日,昭和基地と基地における観測・設営業務を15次越冬隊から引き継ぎ,1976年2月1日,17次越冬隊に,無事,引き渡した.極光,地磁気,電離層,気象,自然地震,潮汐の,いわゆる定常観測は異状なく実施し得た.重点観測項目である,地質,地理,測地からなる地学総合研究,地球化学,生物,医学からなる環境科学総合研究を,主として野外調査により実施した.また,地磁気,極光,電波科学の研究観測を行った.航空機セスナによる航空写真撮影は順調に進み,東経30度線までの海岸線の撮影をすることができた. また,リーセル・ラルセン半島東岸では,コウテイペンギンのルッカリーが発見された.やまと山脈の地質調査を行った旅行隊は,やまと山脈周辺で,隕鉄2箇を含む307箇の隕石を採集した. The 16th wintering party of the Japanese Antarctic Research Expedition (1975-1976) consisting of thirty members was in charge of research activities at Syowa Station for the period from February 1975 to January 1976. The research programes comprised many items in various disciplines, namely, aurora, geomagnetism, ionosphere, meteorology, oceanography, seismology, cartography, geology, geomorphology, geochemistry, biology and medical science. The emphasis was laid on the last six disciplines. Three field parties were dispatched for geological, geomorphological, and biological surveys of the ice-free areas along the Soya Coast in May, August and October 1975. An oversnow traverse for geological and geodesical survey in the Yamato Mountains area was conducted from November 1975 to January 1976. Search and collection of meteorites was attempted and 307 meteorites including two iron meteorites were discovered around the Yamato Mountains. Samplings of snow for chemical analysis were carried out at Mizuho Camp (now Mizuho Station) in September and also en route between Syowa and Mizuho in January, May and October 1975. The single-engine monoplane, Cessna A185F was operated for aerophotographical survey in the areas covering the Prince Olav Coast, the Soya Coast and the coastal area between 30° and 35°E; the Yamato Mountains area and the Belgica Mountains area. By the plane, an Emperor Penguin rookery was discovered on the sea ice of the east coast of the Liiser-Larsen Peninsula and population census of Adelie Penguin and Weddell seal was also carried out. departmental bulletin paper